The Influences of Competence, Work Discipline, and Compensation on Employee Performance - Lubis, Andien Alfaiza; Santoso, Bowo (Manunggal Halim Jaya, 2026)
The purpose of this study was to analyze the influence of competence, work discipline, and compensation on employee performance at PT X. This study uses a quantitative approach with data collection techniques through questionnaires to 40 respondents of bus employees and bus conductors at PT X. The sampling technique used is the saturated sampling technique, where all members of the population are sampled. Data is processed using Smart Partial Least Square (SmartPLS) software. The test results show a significant influence between work discipline and compensation on employee performance and competence does not have a significant effect on employee performance.